2021
DOI: 10.1039/d1ta02927d
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich hydrogel with confined plasmonic Cu/carbon cells for efficient solar water purification

Abstract: Designing low-cost and efficient evaporation system to maximize solar energy utilization is of great importance for the emerging solar water purification technologies. Herein, we demonstrate a universal sandwich hydrogel by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Tian et al also proposed a Cu/carbon cells plasmonic photoabsorber under cost consideration, as Cu is of much lower cost as compared to conventional noble metals while presents a broader plasmonic absorption spectrum. [47,48] When Cu nanoparticles expose to air, oxidation of Cu nanoparticles is expected to occur, which is destructive for surface plasmon resonance. [49] Hence, unlike the noble metals, a strategy to anchor Cu nanoparticles is required for Cu protection.…”
Section: Plasmonic Metalsmentioning
confidence: 99%
“…Tian et al also proposed a Cu/carbon cells plasmonic photoabsorber under cost consideration, as Cu is of much lower cost as compared to conventional noble metals while presents a broader plasmonic absorption spectrum. [47,48] When Cu nanoparticles expose to air, oxidation of Cu nanoparticles is expected to occur, which is destructive for surface plasmon resonance. [49] Hence, unlike the noble metals, a strategy to anchor Cu nanoparticles is required for Cu protection.…”
Section: Plasmonic Metalsmentioning
confidence: 99%
“…Common plasmonic nanoparticles used as solar absorbers include Ag, 73–76 Au, 77 CuS, 78–81 Cu, 44,82 and so on. Recently, Wang et al 26 reported novel plasmonic Cu 7 S 4 –MoS 2 –Au composite nanoparticles (CMA NPs) with broad absorption and high photothermal conversion efficiency, which arises from the coupling effect among Cu 7 S 4 , MoS 2 and Au, as well as the comprehensive utilization of their advantages (Fig.…”
Section: Solar–thermal Conversion Enhancementmentioning
confidence: 99%
“…Carbon-based materials have been used as solar absorbers in various studies in recent years, owing to their excellent light absorption over a broad spectrum, ease of preparation, abundance and low cost. Carbon-based materials include activated carbon, 83–86 polymer 76,87–90 or biomass 82,91–95 derived carbide, carbon black 96–101 and various amorphous carbon materials and highly graphitized carbon materials, such as graphene, 56,59,63,74,77,102–122 carbon nanotubes (CNTs) 27,123–130 and their derivatives.…”
Section: Solar–thermal Conversion Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, some efficient evaporators based on different ultrablack materials such as metal nanoparticles, [23][24][25] semiconductors, [26][27][28] carbon materials, [29][30][31][32][33][34] polymers, [35][36][37] and others [38][39][40][41][42] have been reported. However, there are still one or more disadvantages of these evaporators in practical application, such as the use of expensive metals, the strict and complex chemical synthesis process to achieve high absorbance, synthesis process involving high temperature and pressure, and poor durability.…”
Section: Introductionmentioning
confidence: 99%